2003
DOI: 10.1038/sj.onc.1206759
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase oncoprotein, RET/PTC3, induces the secretion of myeloid growth and chemotactic factors

Abstract: Differentiated thyroid carcinomas are the most frequent endocrine neoplasms, but account for few cancer-related deaths. Although the indolent growth of these cancers correlates well with longevity, the biological basis for this good prognosis is not known. In contrast, two of the most frequent autoimmune diseases involve the thyroid suggesting a high propensity for this organ to invoke destructive immunity. Unfortunately, the mechanism linking malignancy and autoimmunity is not clear, although the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
106
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(119 citation statements)
references
References 54 publications
13
106
0
Order By: Relevance
“…In several human tumors, including thyroid cancer and related animal models, it has been observed that tumor angiogenesis correlates with the extent of macrophage infiltration (Russell et al, 2003;Detoraki et al, 2009). To investigate the presence of infiltrating macrophages in our in vivo tumor model, we evaluated their presence at tumor edges by immunohistochemistry with F4/80 antibodies.…”
Section: Effect Of Timp3 Restoration In Mouse Tumor Xenograftsmentioning
confidence: 99%
“…In several human tumors, including thyroid cancer and related animal models, it has been observed that tumor angiogenesis correlates with the extent of macrophage infiltration (Russell et al, 2003;Detoraki et al, 2009). To investigate the presence of infiltrating macrophages in our in vivo tumor model, we evaluated their presence at tumor edges by immunohistochemistry with F4/80 antibodies.…”
Section: Effect Of Timp3 Restoration In Mouse Tumor Xenograftsmentioning
confidence: 99%
“…The association of RET/PTC with HT suggested that oncoproteins may be one component involved in promoting organ-specific inflammation. While the mechanism of how RET/PTC contributes to autoimmune thyroiditis is not clear, the activated tyrosine kinase activity associated with RET/PTC has been shown to support the production of inflammatory mediators and induce inflammation (Russell et al, 2003). One member of this oncoprotein family RP3 (RP3) can induce nuclear NF-kB activity and the downstream effects of this activation including the production of the Gmcsf and Mcp1 from thyroid cells in vitro and in vivo (Russell et al, 2003(Russell et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…While the mechanism of how RET/PTC contributes to autoimmune thyroiditis is not clear, the activated tyrosine kinase activity associated with RET/PTC has been shown to support the production of inflammatory mediators and induce inflammation (Russell et al, 2003). One member of this oncoprotein family RP3 (RP3) can induce nuclear NF-kB activity and the downstream effects of this activation including the production of the Gmcsf and Mcp1 from thyroid cells in vitro and in vivo (Russell et al, 2003(Russell et al, , 2004. Furthermore, cytokine synthesis was largely dependent on a tyrosine at position 588 of RET/PTC, which corresponds to tyrosine 1062 of c-RET, a Shc docking site critical for downstream signaling (Russell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…M a n u s c r i p t Russell et al, 2003Russell et al, , 2004Puxeddu et al, 2005; A c c e p t e d M a n u s c r i p t Small cytokine belonging to the CXC chemokine which activate leukocytes and is often induced by proinflammatory stimuli. It is the key enzyme in prostaglandin biosynthesis.…”
mentioning
confidence: 99%